UTILITY OF FDG PET SCAN VIABILITY ASSESSMENT OF AKINETIC MYOCARDIAL SEGMENTS ON ECHO FOR PREDICTION OF CONTRACTILITY RECOVERY AT SIX MONTHS AFTER CORONARY ARTERY BYPASS SURGERY: A PROSPECTIVE OBSERVATIONAL STUDY - Imran Akram Khanday, Abdul Majid dar, Dr Aamir Rashid, Dr Imran Hafeez, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Heart failure (HF) is a complex clinical syndrome resulting from structural andfunctional impairment of ventricular filling or ejection of blood. Approximately half of the patients with HF have normal left ventricular function, that is, HF with preserved ejection fraction(HFpEF), the balance have HF with reduced ejection fraction (HFrEF). HFpEF generally is defined as a left ventricular ejection fraction of 50% or greater